Gastrointestinal digestibility insights of different levels of coated complex trace minerals supplementation on growth performance of yellow-feathered broilers - Chen, Chuanbin; Qu, Mingren; Liang, Huan; Ouyang, Kehui; Xiong, Zhihui; Zheng, Youchang; Yan, Qiuliang; Xu, Lanjiao (Frontiers in Veterinary Science, 2022)
This study was designed to evaluate the determine optimum additional level of coated complex trace minerals (TMs) and its impacts on the growth performance of broilers through measurement of digestibility of nutrients and intestinal development. In a 56- day trial, a total of 360 one-day-old male yellow-feathered broilers were randomly divided into 6 dietary treatment groups. Each treatment contained 6 replicates, with 10 birds. The control group supplemented with 1000 mg/kg uncoated complex TMs in the basal diet (UCCTM1000). The remaining 5 treatments were degressively supplemented with coated complex TMs from 1000 mg/kg to 200 mg/kg in the basal diet, which were considered as (CCTM1000), (CCTM800), (CCTM600), (CCTM400), (CCTM200), respectively. Results: compared with the UCCTM1000 supplementation, the CCTM1000 supplementation decreased the feed to gain ratio (F/G) (P < 0.05), increased digestibility of crude protein (CP) (P < 0.05), crude fat (CF) (P < 0.05), villus height (VH) of duodenum (P < 0.05), and the mRNA expression level of occludin in jejunal mucosa (P < 0.05). In addition, the F/G was lower in the CCTE600 group than that in the CCTE200 group (P < 0.05). The villus height to crypt depth ratio (V/C) of jejunum and ileum in the CCTM400 and CCTM600 groups was higher (P < 0.05) than that in the CCTM1000 group. The serum endotoxin and D-lactate level, and CP digestibility were increased by dietary coated complex TMs addition level. The mRNA expression levels of claudin-1, and ZO-1 in the CCTM600 group were higher (P < 0.05) than that in the CCTM1000 group. In conclusion, adding 600 mg/kg coated complex TMs showed the minimum F/G, and the maximum crude protein digestibility and intestine development of yellow-feathered broilers compared with other treatments. This supplementation level of coated complex TMs could totally replace 1000 mg/kg uncoated complex TMs to further decrease the dose of TMs as well as raise economic benefit.